SYAHWAT DALAM AL-QUR’AN - Ulya Hikmah Sitorus Pane (UIN Sayyid Ali Rahmatullah Tulungagung, 2016)
This paper aims to find out the views of the Koran about lust. The Koran describes lust with things associated with pleasure and usually tend to lead to negative things. Lust has positive and negative effects. On the positive side, lust is the strongest driving factor of the human psyche; ladder towards perfection; internal struggle of the human spirit. However, the negative side, lust lead people away from the truth; resulting in fallen human glory. Lustcan also bring disaster if filled with exceeded the limit.Keywords: Lust, Koran, Exegesis